Hurdles at work: perceptions of hospital food handlers - Sigulem Dirce; Rezende Magda; Bertin Cilce; Morais Tania (BMC, 2009)
Abstract Background Food handlers have a very important role in preventing food contamination during its preparation and distribution. This responsibility is even greater in hospitals, since a large number of patients have low immunity and consequently food contamination by pathogenic bacteria could be particularly harmful. Therefore, a good working environment and periodic training should be provided to food handlers by upper management. Methods This study is qualitative research by means of focus group and thematic content analysis methodologies to examine, in detail, the statements by food handlers working in the milk and specific-diet kitchens in a hospital to understand the problems they face in the workplace. Results We found that food handlers are aware of the role they play in restoring patients' health; they consider it important to offer a good-quality diet. However, according to their perceptions, a number of difficulties prevent them from reaching this aim. These include: upper management not prioritizing human and material resources to the dietetic services when making resource allocation decisions; a perception that upper management considers their work to be of lesser importance; delayed overtime payments; lack of periodic training; managers lacking administrative skills; insufficient dietitian staff assistants, leading to overwork, at the same time as there is an excess of dietitians; unhealthy environmental working conditions - high temperature, high humidity, loud and constant noise level, poor ventilation; lack of food, and kitchen utensils and equipment; and relationship conflicts with chief dieticians and co-workers. Conclusion From these findings, improvement in staff motivation could be achieved by considering non-financial incentives, such as improvement in working conditions and showing appreciation and respect through supervision, training and performance appraisal. Management action, such as investments in intermediary management so that managers have the capacity to provide supportive supervision, as well as better use of performance appraisal and access to training, may help overcome the identified problems.